Age-related outcomes in patients undergoing coronary angiography: In which subgroups does age matter? : Results from a large-scale retrospective registry - Kuhn, Lasse; Schupp, Tobias; Steinke, Philipp; Dudda, Jonas; Abumayyaleh, Mohammad S. A.; Weidner, Kathrin; Bertsch, Thomas; Rusnak, Jonas; Akın, Ibrahim; Behnes, Michael (Journal of Clinical Medicine, 2025)
Background: The study investigates age-related differences in the prevalence and extent of coronary artery disease (CAD), as well as long-term outcomes in a large cohort of unselected patients undergoing invasive coronary angiography (CA). The aging population, along with an increasing number of older and multi-morbid patients undergoing CA, poses challenges for healthcare systems. Despite this, studies investigating age-related differences in the long-term outcomes of unselected patients undergoing CA are limited. Methods: Consecutive patients undergoing invasive CA from 2016 to 2022 were included from one institution. The prognosis of patients undergoing CA stratified by pre-specified age groups (i.e., 40-<60, 60-<80 and ≥80 years) was investigated with regard to the primary endpoint of rehospitalization for heart failure (HF), as well as the risks of acute myocardial infarction (AMI) and coronary revascularization at 36 months. Results: From 2016 to 2022, 7520 patients undergoing CA were included with a median age of 70 years (mean: 69 years). The prevalence of CAD (61.9% vs. 71.8% vs. 77.3%; p = 0.001), as well as the prevalence of three-vessel CAD (21.0% vs. 31.5% vs. 36.1%) increased with age. At 36 months, patients ≥ 80 years of age had the highest rates of rehospitalization for HF, followed by patients 60-<80 years and patients 40-<60 years (28.4% vs. 23.2% vs. 14.0%; p = 0.001). Consequently, compared to younger patients (i.e., 40-<60 years of age), those ≥80 years of age exhibited the highest risk of HF-related rehospitalization (≥ 80 years: HR = 2.205; 95% CI 1.884-2.579; p = 0.001), followed by those 60-< 80 years (HR = 1.765; 95% CI 1.536-2.029; p = 0.001). The increased risk of rehospitalization for HF at 36 months was still observed after multivariable adjustment (i.e., ≥80 years: HR = 1.265; 95% CI 1.049-1.524; p = 0.014; 60-<80 years: HR = 1.339; 95% CI 1.145-1.565; p = 0.001) and was specifically evident in patients with left ventricular ejection fraction ≥ 35% and in patients without evidence of CAD/single-vessel CAD. In contrast, the rates of AMI and coronary revascularization at 36 months did not differ significantly among different age groups. Conclusions: Advanced age is an independent predictor of rehospitalization for HF in patients undergoing CA, but not AMI and revascularization during long-term follow-up. This highlights the importance of optimizing diagnostic and therapeutic strategies for HF, particularly in older patients undergoing CA.
Gesehen am 14.07.2025